Pregnancy Class Model for High-Risk Pregnant Women (RESTIKOL) - Sudarmi Sudarmi; Bertalina Bertalina; Fitriana Fitriana; Dewi Yunarti; Monica Dara Delia Suja (Universitas Aisyah Pringsewu, 2022)
The main causes of maternal death in Indonesia are bleeding and hypertension during pregnancy. Maternal mortality can be prevented by strengthening health services and increasing the knowledge of pregnant women about their pregnancy. To make the class of pregnant women effective, a strategy is needed to develop a class model for pregnant women that is intended for pregnant women who are at high risk, which is called RESTIKOL. The purpose of this study is to obtain a class model that focuses on high-risk pregnant women. This type of research is Research and development (RnD) developed by Borg and Gall. Data collection techniques are interviews, study documentation, and FGDs. The model trial was conducted on 100 pregnant women 20-32 weeks in five classes of pregnant women in the South Lampung district. Qualitative data analysis with data validation, classification and triangulation, and quantitative data using analytical descriptive. The results of this study are RESTIKOL class development model for pregnant women, planning for implementing teams consisting of several health professions, in the implementation: screening of pregnant women, the material provided in the form of audio-visual media, cross-sectoral collaboration and programs, and monitoring and mentoring for pregnant women at risk. The step-by-step procedure model for pregnant women for high-risk pregnant women RESTIKOL is ready to be used and feasible to be implemented in our health system. Recommendations for further research on pregnant women are implemented by application/online. Abstrak: Penyebab utama kematian ibu di Indonesia oleh karena perdarahan dan hypertensi dalam kehamilan. Kematian ibu dapat di cegah dengan penguatan pelayanan kesehatan dan meningkatkan pengetahuan ibu hamil tentang kehamilannya. Untuk mengefektifkan kelas ibu hamil agar hasil yang didapat bisa mencapai optimal diperlukan strategi dengan mengembangkan model kelas ibu hamil yang diperutukan bagi ibu hamil yang beresiko Tinggi yang di beri nama kelas ibu hamil RESTIKOL. Tujuan penelitian mendapatkan model kelas ibu hamil yang di fokuskan bagi ibu hamil yang beresiko tinggi. Jenis penelitian Reseach and depelovment (RnD) yang di kembangkan oleh Borg dan Gall. Teknik pengumpulan data dengan: wawancara, study dokumentasi, dan FGD. Uji coba model dilakukan pada 100 ibu hamil usia kehamilan 20-32 minggu di lima kelas ibu hamil wilayah kabupaten lampung selatan. Analisis data kualitatif dengan validasi data, klasifikasi dan triangulasi dan data kuantitatif menggunakan deskriptif analitik. Hasil model pengembangan Kelas ibu hamil RESTIKOL, perencanaan tim pelaksana terdiri dari beberapa profesi Kesehatan, pada pelaksanaan: dilakukan skrining ibu hamil, materi diberikan dalam bentuk media Audio-visual adanya kerjasama lintas sectoral dan program, serta dilakukan pemantaua da pendampingan pada ibu hamil yang beresiko. Kesimpulan Model prosedur langkah pelaksanaan kelas ibu hamil untuk ibu hamil beresiko tinggi RESTIKOL siap dimanfaatkan/layak untuk di laksanakan di lapangan. Rekomendasi untuk dilakukan penelitian lanjutan kelas ibu hamil di laksanakan secara aplikasi/online.